2015
DOI: 10.1002/eat.22386
|View full text |Cite
|
Sign up to set email alerts
|

Development of a smartphone application for eating disorder self‐monitoring

Abstract: Smartphone apps have the capacity to reach and engage traditionally underserved individuals with eating disorders at a large scale. Additional work is indicated for the evaluation of the clinical effectiveness of applications for specific user groups and in clinical treatment contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 44 publications
0
114
1
1
Order By: Relevance
“…For example, we found that 'acceptability' was defined very differently across studies, ranging from proxy markers, i.e. utilisation data (Tregarthen et al 2015) to participants' experience of burden (Dennis et al 2015). This highlights the need for more careful delineation and measurement of implementation outcomes in future work (Proctor et al 2011).…”
Section: Strengths and Limitationsmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, we found that 'acceptability' was defined very differently across studies, ranging from proxy markers, i.e. utilisation data (Tregarthen et al 2015) to participants' experience of burden (Dennis et al 2015). This highlights the need for more careful delineation and measurement of implementation outcomes in future work (Proctor et al 2011).…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…• Participants' perception: preference for paper-and-pencil tracking by some participants Clinical impacts: not studied/reported Tregarthen et al (2015) To describe a smartphone app for the self-monitoring of eating disorder symptoms, evaluate characteristics of app …”
Section: Usabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence has demonstrated that mobile health (mHealth) platforms make it possible for healthcare professionals to monitor patient conditions constantly and remotely on the one hand, and on the other hand these mHealth platforms can empower patients to manage their own diseases [2][3][4][5][6][7][8][9][10][11][12]. In other words, mobile technologies may optimize healthcare practices by enabling professionals to conveniently collect and utilize large amounts of patient data in their clinical practice [13,14].…”
Section: Introductionmentioning
confidence: 99%